Production process optimization using pdca and standardized work for a dress manufacturing SME in Lima, Peru - Barrios Garaboa, Enrique Carlos (2025)
This study addresses process optimization in a microenterprise specializing in dressmaking in Peru, which faces high levels of material waste and inefficient production methods. The company had an average monthly material waste rate of 18%, exceeding the values observed in other companies in the sector, impacting costs and sustainability. The PDCA (Plan-Do-Check-Act) methodology was used to identify the root causes of inefficiencies, such as the lack of standardized work methods, improper use of tools, and suboptimal cutting templates. The implemented improvements included transitioning from paper templates to rigid templates, standardizing tracing and cutting processes, and eliminating unnecessary steps in the production process. These interventions reduced production time per dress from 236 to 189 minutes (19.8%), increased annual production capacity by 24.6%, and decreased material waste from 29kg to 16kg (55.6%), resulting in a 44.6% reduction in costs associated with waste from S/7,908 to S/4,380. The findings highlight the effectiveness of lean tools and continuous improvement methods in increasing productivity and reducing waste, offering a scalable model for other microenterprises in the textile sector.